Localizing Development : Does Participation Work? - Mansuri, Ghazala; Rao, Vijayendra (Washington, DC: World Bank, 2013)
The Policy Research Report Localizing Development: Does Participation Work? brings analytical rigor to a field that has been the subject of intense debate and advocacy, and billions of dollars in development ai d. It briefly reviews the history of participatory development and arg ues that its two modalities, community-based development and local dec entralization, should be treated under the broader unifying umbrella o f local development. It suggests that a distinction between organic pa rticipation (endogenous efforts by civic activists to bring about chan ge) and induced participation (large-scale efforts to engineer partici pation at the local level via projects) is key, and focuses on the cha llenges of inducing participation. The report provides a conceptual fr amework for thinking about participatory development and then uses thi s framework to conduct a comprehensive review of the literature. The f ramework develops the concept of “civil society failure” and explains its interaction with government and market failures. It argues that pa rticipatory development, which is often viewed as a mechanism for bypa ssing market and government failures by ”harnessing” civic capacity, o ught to be seen instead as a mechanism that, if done right, could help to repair important civil society failures. It distills literature fr om anthropology, economics, sociology, and political science to outlin e the challenges for effective policy in this area, looking at issues such as the uncertainty of trajectories of change, the importance of c ontext, the role of elite capture and control, the challenge of collec tive action, and the role of the state. The review of the evidence loo ks at a variety of issues: the impact of participatory projects on inc lusion, civic capacity, and social cohesion; on key development outcom es, such as income, poverty, and inequality; on public service deliver y; and on the quality of local public goods. It draws on the evidence to suggest several recommendations for policy, emphasizing the key rol e of learning-by-doing. It then reviews participatory projects funded by the World Bank and finds the majority lacking in several arenas – p articularly in paying attention to context and in creating effective m onitoring and evaluation systems that allow for learning.